2016
DOI: 10.1038/nature17199
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of outer membrane protein insertion by the BAM complex

Abstract: 3Outer membrane proteins (OMPs) play important roles in Gram-negative bacteria, mitochondria and chloroplasts in nutrition transport, protein import, secretion, and other fundamental biological processes [1][2][3] . Dysfunction of mitochondria outer membrane proteins are linked to disorders such as diabetes, Parkinsons and other neurodegenerative diseases 4,5 . The OMPs are inserted and folded correctly into the outer membrane (OM) by the conserved OMP85 family proteins [6][7][8] , suggesting that similar ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

34
462
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(514 citation statements)
references
References 66 publications
34
462
4
1
Order By: Relevance
“…In terms of anaP2-anaP3, this is in line with earlier findings on BamA, where the C-terminal POTRA domains ecP3-ecP5 were assumed to have a rigid architecture (36). However, recent crystal structures of assembled BAM complexes challenge this assumption (8)(9)(10). In addition, the orientation of anaP2-anaP3 in the x-ray structure is well within this structure bundle, and thus seems to be a good representative of this ensemble.…”
Section: Discussionsupporting
confidence: 88%
“…In terms of anaP2-anaP3, this is in line with earlier findings on BamA, where the C-terminal POTRA domains ecP3-ecP5 were assumed to have a rigid architecture (36). However, recent crystal structures of assembled BAM complexes challenge this assumption (8)(9)(10). In addition, the orientation of anaP2-anaP3 in the x-ray structure is well within this structure bundle, and thus seems to be a good representative of this ensemble.…”
Section: Discussionsupporting
confidence: 88%
“…Recent X-ray crystallography and cryo-EM studies reported the structures of several Omp85 family members, including FhaC, TamA, and BamA (28,(36)(37)(38)(43)(44)(45)(46)(47). Given the conservation of key features, these structures serve as models for Toc75, albeit with low sequence identity (7%, 7%, and 8%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The structure reveals that the POTRA domains form an L-shaped structure very similar to BamA, with a unique extended helix within POTRA2 that is not observed in the POTRA domains of BamA and other Omp85 family members (25,28,(35)(36)(37)(38). Based on these unique structural properties, we investigated the contribution of individual POTRA repeats in binding chloroplast precursors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the structure of the Bam complex was recently solved by both X-ray crystallography and cryo-EM (13)(14)(15)(16), the mechanism by which it catalyzes the integration of b-barrel proteins into the OM remains poorly understood. The complex has the shape of a top hat in which the BamA bbarrel forms the crown and the POTRA domains together with the lipoproteins form a brim (14,15).…”
mentioning
confidence: 99%